Combining antiviral drugs with BET inhibitors is beneficial in combatting SARS‐CoV‐2 infection - Arpan Acharya; Tatiana G. Kutateladze; Siddappa N. Byrareddy (Wiley, 2022)
Abstract The COVID‐19 pandemic caused by the novel coronavirus SARS‐CoV‐2 has resulted in more than 500 million cases and 6 million deaths. Several antiviral therapies and vaccines have been developed to mitigate the spread of this infection. However, new approaches are required to battle emerging SARS‐CoV‐2 variants containing mutations that can reduce the vaccines' efficacy. The use of a combination of antiviral drugs with inhibitors of mammalian target of rapamycin (mTOR) signalling pathways has emerged as one of the promising novel approach. In this study, we have shown that SF2523, a dual activity small molecule that inhibits PI3K and BRD4, acts synergistically with the antiviral drugs remdesivir (RDV) and MU‐UNMC‐2. Our findings suggest that the mTOR pathways are necessary for SARS‐CoV‐2 pathogenesis in human cells and that targeting PI3K/BET (bromodomain and extra‐terminal domain proteins) alone or combined with antiviral therapies is beneficial in mitigating SARS‐CoV‐2 and its variants of concern (VOCs).